Considerations Regarding Vocal Technique and Style in Various Treatises from the 17th Century - KARÁCSONY, Noémi; RUCSANDA, Mădălina Dana (Babes-Bolyai University Cluj-Napoca, 2025)
The early 17th century witnessed the establishment of Italian vocal art, that would become a reference point for other vocal idioms and the source of bel canto. Italian singers and their art were considered examples worthy of imitation, numerous German or French sources referring to the vocal mastery of the Italians. The present study aims to present several European treatises of the 17th century — Italian, Spanish, German, and French — gradually revealing the evolution of European vocal art, from the early Baroque and its seconda prattica, to the final decades of the century, marked by the growing dispute between the Italian and French style and vocal technique. Throughout the study, similarities and differences are pointed out, revealing that the requirements regarding vocal technique are rather similar for all the singing idioms. What distinguishes the various schools of singing are aspects related to the particularities of the language, that also leads to the adjustment of certain technical demands. Secondly, questions regarding style or the execution of ornaments seem to set the Italian and French vocal idioms apart. The present article represents the first part of a research that is dedicated to the analysis of various historical sources of the 17th and 18th centuries — as valuable milestones for the establishment of the great 19th century singing methods. Historically informed performances require the singer to become acquainted with the historical period to which a particular composition belongs, its treatises and other theoretical sources of the period, eventually arriving to a better understanding of the score and a more accurate construction and delivery of the vocal discourse. Finally, the authors wish to emphasize that the historical sources referred to in the current study represent only a small portion of the theoretical writings of the period, and that the chosen works were considered representative for the current research — but not necessarily the most important.
Keywords: voice; word-painting; singing; vocal registers; vibrato